Self-Employed in the EU VAT System: An Entrepreneur or an Employee? - Sęk, Małgorzata (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The aim of the study is to indicate, based on the analysis of EU rules on the personal scope of VAT and relevant case law of the CJEU, what circumstances should be taken into account when determining whether a self-employed person is an independent entrepreneur, and therefore a VAT taxpayer providing to his client services subject to VAT, or rather remains with this client in a relationship corresponding to the employment relationship, which places the self-employed and the services provided by him outside the scope of VAT. The study also explains that due to the criterion of economic reality applicable in the EU VAT system, determining the VAT status of a self-employed cannot be based solely on the content of a contract between him and the client, but must take into account the actual course of cooperation. The extensive subject matter of consequences ensuing for the self-employed and his client if tax authorities deny the self-employed the status of an entrepreneur and VAT taxpayer, has been omitted, as it requires a separate study.